Pengaruh Substitusi Bungkil Kedelai dengan Bungkil Wijen Lokal Terhadap Efisiensi Protein dan Performan Ayam Broiler - Isti Astuti (Sains Peternakan: Jurnal Penelitian Ilmu Peternakan, 2007)
The obyective of this experiment was to study the effect of substitution of soybean meal with local sesame meal on performance and protein effisiency ratio of broiler chicken. One hundred of broiler chickens strain Lohman were allocated in Completely Randomized Design with five replication and four chicken of each. The treatments were  P0 :  100% BK+ 0% BWL ;  P1 :  90% BK+ 10% BWL ;  P2 ; 80% BK+ 20% BWL;   P3  :  70% BK+ 30 BWL and  P4 :  60% BK+ 40% BWL. Variable measured were feed consumption,average daily gain, feed conversion and protein efficiency ratio. Data were analyzed with analysis of variance (ANOVA). The result of this research indicated  that treatments were not significant effect to the all variables. Average feed consumption (g/head/d)  of: (92,76; 90,13; 90,87; 87,10 dan 89,31) ; average daily gain (g/head/d) of : (47,16; 45,99; 47,03; 45,46 dan 45,76);  average of feed conversion of : ( 1,95;  1,97; 1,93;  1,96 dan  1,95) and protein efficiency ratio  of : (2,31;  2,27;  2,25;  2,31; dan 2,28)  for P0,  P1,  P2, P3 and P4, respectively. It was concluded that 40% of soybean meal could  be substituted with local sesame meal in diet of broiler  that reared up to 42 days of age. Key words:   soybean meal, local  sesame meal, performance, efficiency protein, broiler